Considerations for the scientific support process and applications to case studies - Ruddock, A. D.; Boyd, C.; Winter, E. M.; Ranchordas, M. (International Journal of Sports Physiology and Performance, 2019)
Case studies are vehicles to bridge the gap between science and practice because they provide opportunities to blend observations and interventions that have taken place in real-world environments with scientific rigor. The purpose of this invited commentary is to present considerations for those providing applied sport science support to athletes with the intention of broadcasting this information to the scientific community. The authors present a 4-phased approach (1: athlete overview; 2: needs analysis; 3: intervention planning; and 4: results, evaluation, and conclusion) for scientific support to assist practitioners in the development and implementation of scientific support. These considerations are presented in the form of "performance questions" designed to guide and critically evaluate the scientific support process and aid the transfer of this knowledge through case studies.